A hybrid decision‐making framework under complex spherical fuzzy prioritized weighted aggregation operators. Issue 6 (14th May 2021) - Akram, Muhammad; Khan, Ayesha; Alcantud, José Carlos R.; Santos‐García, Gustavo
Abstract: Complex spherical fuzzy set, an extended version of spherical fuzzy set, is a very powerful tool to capture fourfold information (typically yes, no, abstain and refusal), in which the range of degrees occurs in the complex plane with unit disk. Through this prominent feature, complex spherical fuzzy sets outperform earlier concepts of fuzzy sets and their extensions. This research article utilizes complex spherical fuzzy sets and prioritized weighted aggregation operators to construct the complex spherical fuzzy prioritized weighted averaging/geometric operators. We present their most noticeable properties. Further, we establish a decision‐making approach that takes full advantage of the aforesaid operators. To explore their superiority and applicability in decision making, we apply our algorithm to a numerical example. Finally, we compare this decision‐making approach with prevailing methods in this context.